Product Discovery Practices of Technology Companies in the Czech Republic - Vedra, Stanislav; Novotný, Ota, 1971-; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
The goal of this thesis is to evaluate product discovery practices in the Czech Republic based on two objectives. The first objective is about analyzing product discovery practices based on literature. The second objective is about interviewing product managers to find out how they carry out product discovery. The evaluation is based on comparison of these two perspectives, i.e., theoretical and practical application of product discovery practices. The interviews were conducted with ten product managers using qualitative semi-structured interviews. The interviews were analyzed by thematic analysis. The evaluation consist of 14 practices, namely double diamond, objectives and key results, outcome-based roadmap, experimental approach, golden circle, value-complexity matrix, jobs to be done, feedback collection, competitive analysis, opportunity solution tree, prototyping, testing, user story mapping, and discovery sprint. All of them were found in the interviews except opportunity solution tree. However, the evaluation indicates that practical application of product discovery practices exceeds theoretical expectations.
Vedoucí práce: Ota Novotný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses